Systemkompetenz: Forschungsstand und Forschungsfragen - Armin Rempfler (Zeitschrift für Geographiedidaktik, 2009)
This article starts with a review of the current state of research with regard to the competence of system thinking and continues by formulating questions relevant to geographical education research. This approach aims at making a substantial contribution to the system concept which is considered the basic concept of geographical education in the German curriculum. Terminological considerations show that it makes sense to use terms like "competence of system thinking" and "system thinking" as synonymous, whereas both don’t incorporate the level of action as well. While an extensive literature review in and outside of geographical sciences documents the broad application of systemic approaches, it also reveals that there is little empirically-based knowledge on this topic. Furthermore, it is evident that the competence of system thinking is composed of several different subcomponents, that there are indications of a domain-independency of the competence of system thinking and that this competence is influenced by interest as well as preliminary knowledge. From a geographical education point of view one of the questions to be explored is which preliminary knowledge of geographical issues learners bring with. With regard to develop models of competency of system thinking there are existing models which can be used, but they all show deficiencies: They consider neither man-environment interactions nor different scales. To afford the high demanded level of this modelling it will be important to cooperate multidisciplinary.